Relevance of Metabolic Profiles in Children With Cardiac Disease - Divanisova, Sandra (Auckland University of Technology, 2023)
Fat is primarily a way to store energy. Fat in the form of fatty acids combines with carnitine to form acylcarnitines and these are transported into the cell’s mitochondria where the fatty acids are released and metabolised to provide energy. Acylcarnitines can be measured in blood and this reflects concurrent fat metabolic status. This acylcarnitine test, along with several amino acids and endocrine markers is performed in all babies born in New Zealand as part of a routine newborn screening test enabling diagnosis of rare genetic metabolic disorders. This data is stored in the newborn metabolic screening laboratory database at Auckland City Hospital. The heart has high energy requirements and fat is the main fuel. The failing heart results in disruption to fatty acid metabolism. It has been recently reported that adults with heart failure have plasma acylcarnitine profiles that differ from the normal population with higher levels of long chain fatty acid derivatives. Babies with severe congenital heart disease can present to hospital in the first two weeks of life. Most of these cases are seen at Starship Children’s Hospital in Auckland. Many of these babies will have stressed myocardium. It is possible that these babies will, like their adult counterparts, have abnormal fat metabolism that can be demonstrated by an abnormal acylcarnitine profile. In addition to congenital heart lesions, the acylcarnitine profiles of children with cardiomyopathy were also reviewed. These children are often admitted to Starship Children’s Hospital and have had full metabolic investigations as part of their diagnostic work-up. The aim of the study was to compare the stored data of the early postnatal metabolic profiles of children with congenital cardiac disease and healthy controls to establish if there is a pattern of metabolites that is similar to that seen in adults with cardiac failure. The findings highlighted elevation of several short and medium chain acylcarnitines indicative of defects in activities of some enzymes and/or transporters in fatty acid metabolic pathways. The study also identified alterations in blood levels of several amino acids, and endocrine markers. However, this study did not observe difference in long chain acylcarnitine levels reported in adult heart failure. This could be partially due to the general anabolic status of the children cohort.